1994
DOI: 10.1089/neu.1994.11.499
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Accumulation After Traumatic Brain Injury in Rats: Comparison of Weight Drop and Controlled Cortical Impact Models

Abstract: Previous work in our laboratory and others using the weight drop (WD) model of traumatic brain injury (TBI) has shown that neutrophils accumulate in brain tissue during the initial 24 h posttrauma as measured by myeloperoxidase (MPO) activity and immunohistochemistry. This study compares the acute inflammatory response to TBI over time, as measured by MPO activity, in the WD and controlled cortical impact (CCI) models. Anesthetized adult Sprague-Dawley rats were traumatized using WD (10-g weight dropped 5 cm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(142 citation statements)
references
References 22 publications
11
131
0
Order By: Relevance
“…4,23,24 However, the specific relationship of cytokines and neurotrophins with the severity of brain injury and with the neurologic outcome remains still controversial. Recent studies have shown that increased levels of IL-1β are associated with increased severity and poor outcome in patients affected by meningitis, hypoxic-ischemic encephalopathy, and traumatic head injuries.…”
Section: Discussionmentioning
confidence: 99%
“…4,23,24 However, the specific relationship of cytokines and neurotrophins with the severity of brain injury and with the neurologic outcome remains still controversial. Recent studies have shown that increased levels of IL-1β are associated with increased severity and poor outcome in patients affected by meningitis, hypoxic-ischemic encephalopathy, and traumatic head injuries.…”
Section: Discussionmentioning
confidence: 99%
“…A profound inflammatory response has been documented, initiated immediately after experimental TBI (34,35), which is characterized by the release of several cytokines (4). It has been suggested that TNF plays a detrimental role in the acute pathophysiology of TBI and ischemia (2, 8, 16, 36, 37).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response in the CNS may have various consequences on outcome, depending upon the degree of inflammatory response and when it occurs (Blight, 1985;Benveniste, 1992). Both acute and chronic inflammatory processes have been shown to influence outcome in various experimental models of cerebral ischemia and trauma (Arvin et al, 1996;Clark et al, 1994;del Zoppo et al, 2000;Fan et al, 1995;Fan et al, 1996;Feuerstein et al, 1998;Kochanek and Hallenbeck, 1992). While acute inflammatory events may participate in secondary injury processes, more delayed inflammatory events may be reparative (Bethea and Dietrich, 2002;Kerschensteiner et al, 1999).…”
Section: Inflammationmentioning
confidence: 99%